2021
DOI: 10.1038/s41598-021-95438-0
|View full text |Cite
|
Sign up to set email alerts
|

Social engagement and cognitive function among middle-aged and older adults: gender-specific findings from the Korean longitudinal study of aging (2008–2018)

Abstract: Recent findings suggest that social disengagement in later life may result in cognitive decline and increase risk of Alzheimer’s and related dementias. However, little is known regarding the gender-specific longitudinal association between social engagement and cognition among middle-aged and older adults. Using data from a nationally representative sample of 2707 men and 5196 women from the Korean longitudinal study of aging, we examined the gender-specific association between social activity and cognitive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The COVID-19 pandemic has called for international attention on the importance of social relationships/social engagement/social inclusion in terms of supporting the physical, emotional and cognitive health of older adults 66 67. Evidence suggests significant correlations exist between engaging in social activities and enhanced cognitive outcomes 10 50. However, depression and other mental illnesses that may lead to reduced social networks and activities resulting in cognitive decline among older adults are little explored, especially in LMICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has called for international attention on the importance of social relationships/social engagement/social inclusion in terms of supporting the physical, emotional and cognitive health of older adults 66 67. Evidence suggests significant correlations exist between engaging in social activities and enhanced cognitive outcomes 10 50. However, depression and other mental illnesses that may lead to reduced social networks and activities resulting in cognitive decline among older adults are little explored, especially in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed a greater female disadvantage and theorised gender as the crucial factor to be considered in understanding the differences in cognitive functioning in Indian context 46–48. Also, studies have shown the significant gender differences in the association between social engagement and cognitive functioning 49 50. Thus, the study also explored the moderation effects of gender in the relationship between social engagement and cognitive functioning.…”
Section: Introductionmentioning
confidence: 96%
“…The Korea Employment Information Service has performed this survey every two years since 2006. The survey data has been used by several prior studies [ 66 , 67 , 68 , 69 ]; such works could ensure the quality of the data. The study period of this research is between 2008–2016.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, effective communication is crucial for older adults to adjust to health and lifestyle changes (Yorkston et al, 2010) which might come with retirement, for example. Indeed, social engagement is associated with better cognitive functioning (Gow et al, 2013;Pichora-Fuller et al, 2015;Oh et al, 2021) and may reduce the risk of dementia (Fratiglioni et al, 2004). Continued theoretical development in this area is therefore required.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%